KINETIC PROCESSES IN ALUMINUM PLASMA - Akbar, A. Zh. (Recent Contributions to Physics, 2008)
The phase shifts and the scattering cross section of electron-ion and electron-atom interaction in dense semi-classical aluminum plasma are investigated. Shown that the taking into account charge screening effect at the long distance and the quantum effects of diffraction in interaction between charge particles leads to reduction of the phase shifts and the scattering cross sections. The task has solved quantum-mechanically by Calogero equation.